2009
DOI: 10.1093/ije/dyp329
|View full text |Cite
|
Sign up to set email alerts
|

Comparative appraisal of educational inequalities in overweight and obesity among adults in 19 European countries

Abstract: In most European countries, people of lower educational attainment are now most likely to be overweight or obese. An increasing level of socio-economic development was associated with an emergence of inequalities among men, and a persistence of these inequalities among women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
133
8
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(183 citation statements)
references
References 37 publications
23
133
8
14
Order By: Relevance
“…It may be linked to the higher consumption of energy-dense foods and increased sedentary activity (37)(38)(39)(40) among males in this age group. Growing evidence suggests that overweight and obesity are socially patterned (41,42) and may also be linked to the cultural environment (43,44) and cultural practice of food distribution and consumption within households locally (45) . In fact, our report of dietary intakes in this population suggests that more girls consumed fruit and vegetables at least five times per week, while twice as many boys were in the highest tertile for soda and fizzy beverage consumption (A Ramcharitar-Bourne, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…It may be linked to the higher consumption of energy-dense foods and increased sedentary activity (37)(38)(39)(40) among males in this age group. Growing evidence suggests that overweight and obesity are socially patterned (41,42) and may also be linked to the cultural environment (43,44) and cultural practice of food distribution and consumption within households locally (45) . In fact, our report of dietary intakes in this population suggests that more girls consumed fruit and vegetables at least five times per week, while twice as many boys were in the highest tertile for soda and fizzy beverage consumption (A Ramcharitar-Bourne, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the difference between eastern and western Turkey (11) at the τth quantile of BMI can be decomposed into composition and structural effects as follows: (13) (14) (15) then structural and composition effect can be written in terms of the sum of contribution of each covariate as: (16) (17) where indicates the omitted group effect, and indicate the element of and at quartile respectively. and are the respective contributions of the covariate to composition and structure effect at quartile [44].…”
Section: Methodsmentioning
confidence: 99%
“…Robert and Reither [4] investigated obesity in the United States and indicated that individuals with lower socio-economic status (SES) have higher rates of obesity. Wamala et al [8], Kleiser et al [5] and Roskam et al [11] investigated the prevalence of obesity in Sweden, Germany, and nineteen European countries…”
Section: Introductionmentioning
confidence: 99%
“…Otros estudios demostraron asociaciones divergentes entre esas variables. En países desarrollados la prevalencia de exceso de peso es mayor en individuos con baja escolaridad (33,34) . Ya, en los países en desarrollo, se percibe una asociación positiva entre el exceso de peso y el aumento de los años de estudio para el sexo masculino, mientras que para el sexo femenino la asociación es inversa (23) .…”
Section: Nº 44 Octubre 2016unclassified